A Multidisciplinary Curriculum to Standardize Chest Procedures Training for Trainees in General Surgery, Emergency Medicine, and Critical Care - Jacob LoMonaco; Robert J. Klemisch; Jonathan S. Ilgen; Beth Sobba; Jenelle Badulak; Thomas K. Varghese; Amy E. Morris (Association of American Medical Colleges, 2024)
Introduction Critical care, emergency medicine, and surgical trainees frequently perform surgical and Seldinger-technique tube thoracostomy, thoracentesis, and thoracic ultrasound. However, approaches to teaching these skills are highly heterogeneous. Over 10 years, we have developed a standardized, multidisciplinary curriculum to teach these procedures. Methods Emergency medicine residents, surgical residents, and critical care fellows, all in the first year of their respective programs, underwent training in surgical and Seldinger chest tube placement and securement, thoracentesis, and thoracic ultrasound. The curriculum included preworkshop instructional videos and 45-minute in-person practice stations (3.5 hours total). Sessions were co-led by faculty from emergency medicine, thoracic surgery, and pulmonary/critical care who performed real-time formative assessment with standardized procedural steps. Postcourse surveys assessed learners' confidence before versus after the workshop in each procedure, learners' evaluations of faculty by station and specialty, and the workshop overall. Results One hundred twenty-three trainees completed course evaluations, demonstrating stable and positive responses from learners of different backgrounds taught by a multidisciplinary group of instructors, as well as statistically significant improvement in learner confidence in each procedure. Over time, we have made incremental changes to our curriculum based on feedback from instructors and learners. Discussion We have developed a unique curriculum designed, revised, and taught by a multidisciplinary faculty over many years to teach a unified approach to the performance of common chest procedures to surgical, emergency medicine, and critical care trainees. Our curriculum can be readily adapted to the needs of institutions that desire a standardized, multidisciplinary approach to thoracic procedural education.